Resin film for terminal of all-solid-state battery and all-solid-state battery
Patent Information
- Application Number
- JP2024155302
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-02-10
- Estimated Expiration
- 2042-02-02
AI Technical Summary
The resin film for terminals of all-solid-state batteries generates air bubbles when heat-sealed to a metal terminal, leading to potential sealing strength loss and gas leakage due to moisture evaporation and reaction with sulfide-based solid electrolytes.
A resin film with a moisture content of 2,700 ppm or less, composed of a multilayer structure including an insulating layer and sealant layers with specific resin compositions, such as acid-modified polyolefin and polyester, to suppress bubble generation and maintain sealing integrity.
The solution effectively prevents air bubble formation and maintains sealing strength, even in high-temperature environments, reducing gas leakage and moisture intrusion, thereby ensuring the integrity of the all-solid-state battery.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin film for a terminal of an all-solid-state battery and an all-solid-state battery. [Background technology]
[0002] In recent years, the development of all-solid-state batteries that can increase capacity has progressed rapidly. Unlike current lithium-ion batteries, all-solid-state batteries use a solid electrolyte, which allows them to be used at high temperatures that were not possible until now. This eliminates the need for battery cooling equipment, and is expected to lead to improved space efficiency, reduced costs, and lower power consumption.
[0003] Such an all-solid-state battery comprises an outer bag that houses the battery body, such as a solid electrolyte and electrodes, and a metal terminal called a tab for extracting current from the battery body. A portion of the outer peripheral surface of the metal terminal is covered with a terminal resin film (sometimes called a "tab sealant").
[0004] Conventionally, such a resin film for terminals has been known, for example, as described in Patent Document 1. This document discloses a resin film for terminals that is made of a resin composition that has adhesion to a current extracting terminal, and that contains a thermoplastic resin having a melting point of 160°C or higher and does not contain a thermoplastic resin having a melting point of less than 160°C. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2020 / 004412 Summary of the Invention [Problem to be solved by the invention]
[0006] However, the resin film for terminals of the all-solid-state battery described in the above-mentioned Patent Document 1 has the following problems. That is, when the resin film for terminal described in the above Patent Document 1 is heat-sealed to a metal terminal, air bubbles are sometimes found to be generated all over the resin film for terminal.
[0007] The present disclosure has been made in consideration of the above problems, and aims to provide a resin film for a terminal of an all-solid-state battery, which can suppress the generation of air bubbles when heat-sealed to a metal terminal, and an all-solid-state battery. [Means for solving the problem]
[0008] The present inventors have studied the cause of the phenomenon in which air bubbles are observed all over the surface of the resin film for terminals as described above. As a result, they have considered that the reason why air bubbles are observed all over the surface of the resin film for terminals is that the resin film for terminals is heat-sealed to the metal terminal at a high temperature. That is, the present inventors have considered that when the resin film for terminals is heat-sealed to the metal terminal at a high temperature, the moisture in the resin film for terminals is evaporated, and the generated air bubbles expand all at once, easily combine with other air bubbles, grow, and remain after cooling. In addition, the present inventors have considered that the above phenomenon is largely dependent on the moisture content in the resin film for terminals. Therefore, the present inventors have further conducted intensive research and have found that the above problem can be solved by the following disclosure.
[0009] That is, the present disclosure relates to a resin film for a terminal of an all-solid-state battery that is bonded by heat sealing to an outer peripheral surface of a part of a metal terminal that is electrically connected to a battery body that constitutes an all-solid-state battery, the resin film for a terminal of an all-solid-state battery having a moisture content of 2700 ppm by mass or less.
[0010] According to the above-mentioned resin film for terminal, when the resin film for terminal is heat-sealed to the outer peripheral surface of a part of a metal terminal, the generation of bubbles in the resin film for terminal can be suppressed. Therefore, the generation of coarse parts (parts with many bubbles) and dense parts (parts with few bubbles) in the resin film for terminal, which causes the seal strength to the metal terminal to be reduced in the coarse parts, is suppressed. Therefore, even if the battery body including the solid electrolyte expands due to the use of the all-solid-state battery in a high-temperature environment and a force acts on the exterior bag to open it, the resin film for terminal can maintain the sealed state of the exterior bag. Therefore, even if gas such as hydrogen sulfide is generated in the exterior bag of the all-solid-state battery by the reaction between moisture and the sulfide-based solid electrolyte in the exterior bag of the all-solid-state battery when the all-solid-state battery contains a sulfide-based solid electrolyte as a solid electrolyte, leakage of such gas can be suppressed. Furthermore, the generation of bubbles that easily become a passage for moisture is suppressed in the resin film for terminal, so that the intrusion of moisture from the outside of the exterior material into the resin film for terminal is suppressed. Therefore, when the all-solid-state battery contains a sulfide-based solid electrolyte as a solid electrolyte in an outer bag, it is possible to suppress the generation of hydrogen sulfide due to a reaction between moisture and the sulfide-based solid electrolyte.
[0011] The resin film for a terminal is preferably made of a multilayer film having an insulating layer and a sealant layer provided on at least one side of the insulating layer.
[0012] In this case, it becomes possible to separate the functions of the resin film for the terminal. That is, the insulating layer ensures the thickness of the resin film for the terminal, and the insulation properties during heat sealing are secured. Meanwhile, the sealant layer can fill the gap between the resin film for the terminal and the metal terminal. Even if the sealant layer is fluidized during heat sealing of the resin film for the terminal to the metal terminal, causing variations in the insulation properties of the sealant layer, the insulating layer ensures the thickness of the resin film for the terminal, and thus stable insulation properties are secured.
[0013] In the resin film for a terminal, the sealant layer of the multilayer film is preferably an acid-modified polyolefin resin layer.
[0014] In this case, since the acid-modified polyolefin resin layer has excellent adhesion to metal, the adhesion between the sealant layer of the resin film for terminal and the metal terminal can be further improved.
[0015] The resin film for a terminal is preferably a polyolefin film containing a polyolefin resin or a polyester film containing a polyester resin.
[0016] In this case, the all-solid-state battery has better sealing properties for the metal terminals and the outer bag. In addition, since the polyolefin film and the polyester film have heat resistance, the terminal resin film can further improve the heat resistance of the all-solid-state battery.
[0017] The resin film for a terminal preferably has a melting point of 250° C. or lower.
[0018] In this case, since the resin film for terminal has a melting point of 250°C or less, the heat sealing temperature can be reduced. Therefore, when the resin film for terminal is heat sealed to a metal terminal, the generation of air bubbles in the resin film for terminal can be further suppressed. Therefore, the decrease in the seal strength and barrier property of the resin film for terminal can be further suppressed. Therefore, the resin film for terminal can more sufficiently maintain the sealing property of the outer bag of the all-solid-state battery. In addition, the resin film for terminal can also suppress the intrusion of moisture through the resin film for terminal.
[0019] The resin film for a terminal preferably has a melting point of 150° C. or higher.
[0020] In this case, since the terminal resin film has a melting point of 150° C. or more, even if the terminal resin film is used in a high-temperature environment, it is possible to suppress a decrease in the seal strength of the terminal resin film with respect to the metal terminal. Therefore, when the all-solid-state battery contains a sulfide-based solid electrolyte as a solid electrolyte in an outer bag, even if gas such as hydrogen sulfide is generated by a reaction between moisture and the sulfide-based solid electrolyte in the outer bag of the all-solid-state battery, leakage of such gas can be further suppressed.
[0021] The present disclosure also relates to an all-solid-state battery comprising: a battery body containing a solid electrolyte; a metal terminal electrically connected to the battery body; an outer bag that holds the metal terminal and contains the battery body; and a terminal resin film that is bonded to an outer peripheral surface of a portion of the metal terminal by heat sealing, wherein the terminal resin film is made of the above-mentioned terminal resin film.
[0022] According to this all-solid-state battery, the terminal resin film is bonded to a part of the outer peripheral surface of the metal terminal by heat sealing. Here, according to the above-mentioned terminal resin film, when the terminal resin film is heat-sealed to the metal terminal, the generation of air bubbles in the terminal resin film can be suppressed. Therefore, according to the all-solid-state battery of the present disclosure, the occurrence of rough and dense parts in the terminal resin film, which causes the seal strength to the metal terminal to decrease in the rough parts, is suppressed. Therefore, even if the battery body expands due to use of the all-solid-state battery in a high-temperature environment and a force acts on the outer bag to open it, the all-solid-state battery can maintain the sealed state of the outer bag by the terminal resin film. In addition, the occurrence of air bubbles that easily become a passage for moisture is suppressed in the terminal resin film, so that the intrusion of moisture from the outside of the all-solid-state battery is suppressed.
[0023] In this disclosure, "melting point" means the "peak melting temperature" determined in accordance with the method described in JIS K7121-1987, and when two or more melting peaks appear independently, the lowest melting peak temperature is adopted.
[0024] In addition, in the present disclosure, when the resin film for a terminal is a multilayer film, the melting point refers to the melting point of the layer that has the lowest melting point among the layers constituting the multilayer film. Effect of the Invention
[0025] According to the present disclosure, there are provided a resin film for a terminal of an all-solid-state battery, which can suppress the generation of air bubbles when heat-sealed to a metal terminal, and an all-solid-state battery. [Brief description of the drawings]
[0026] [Figure 1] FIG. 2 is a cross-sectional view that illustrates a terminal resin film of an all-solid-state battery according to an embodiment of the present disclosure. [Diagram 2] FIG. 1 is a perspective view showing an all-solid-state battery according to an embodiment of the present disclosure. [Diagram 3] 3 is a partial cross-sectional view taken along line AA of the resin film for terminal and the metal terminal shown in FIG. 2. [Figure 4] FIG. 2 is a cross-sectional view that illustrates a schematic example of the exterior material illustrated in FIG. [Diagram 5] FIG. 2 is a cross-sectional view illustrating a terminal resin film according to another embodiment of the present disclosure. [Figure 6] FIG. 2 is a plan view showing a structure for obtaining evaluation samples in Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] Hereinafter, preferred embodiments of the present disclosure will be described with reference to the drawings. In the drawings, the same or corresponding parts are denoted by the same reference numerals, and duplicated explanations will be omitted. In addition, the dimensional ratios of the drawings are not limited to the ratios shown in the drawings.
[0028] [Resin film for terminals of solid-state batteries] FIG. 1 is a cross-sectional view that shows a schematic diagram of a terminal resin film of an all-solid-state battery according to an embodiment of the present disclosure. As shown in FIG. 1, a terminal resin film (hereinafter, also simply referred to as a "terminal resin film") 10 of the all-solid-state battery according to this embodiment includes a first sealant layer 1, an insulating layer 2, and a second sealant layer 3 in this order. That is, the terminal resin film 10 is a multi-layer film. The moisture content of the terminal resin film 10 is 2700 mass ppm or less. The terminal resin film 10 may have an adhesive layer that bonds the first sealant layer 1 and the insulating layer 2. The terminal resin film 10 may have an adhesive layer that bonds the second sealant layer 3 and the insulating layer 2.
[0029] The resin film 10 for terminals can suppress the generation of air bubbles in the resin film 10 for terminals when the resin film 10 for terminals is heat-sealed to a metal terminal, as compared with a case where the moisture content of the resin film 10 for terminals exceeds 2700 ppm by mass. In addition, since the resin film 10 for terminals is made of a multilayer film including an insulating layer 2 and a first sealant layer 1 and a second sealant layer 3 provided on both sides of the insulating layer 2, the resin film 10 for terminals can be functionally separated. That is, the insulating layer 2 ensures the thickness of the resin film 10 for terminals, and the insulation property during heat sealing is ensured. On the other hand, the first sealant layer 1 can fill the gap between the resin film 10 for terminals and the metal terminal. On the other hand, the second sealant layer 3 can be heat-sealed (thermally fused) to an exterior bag of an all-solid-state battery. Furthermore, even if the first sealant layer 1 becomes fluid when the resin film 10 for the terminal is heat-sealed to the metal terminal, causing variation in the insulating properties of the first sealant layer 1, the thickness of the resin film 10 for the terminal is guaranteed by the insulating layer 2, thereby ensuring stable insulation properties.
[0030] The moisture content of the resin film 10 for a terminal may be 2700 ppm by mass or less, preferably 2000 ppm by mass or less, and more preferably 1500 ppm by mass or less. The moisture content of the resin film 10 for a terminal may be 0 ppm by mass.
[0031] It is sufficient that the resin film for terminal 10 has an overall moisture content of 2700 ppm by mass or less. Thus, the first sealant layer 1, the insulating layer 2, and the second sealant layer 3 may each have a moisture content of 2700 ppm by mass or less, but even if some layers have a moisture content of 2700 ppm by mass or less and the remaining layers have a moisture content greater than 2700 ppm by mass, it is sufficient that the overall moisture content is 2700 ppm by mass or less.
[0032] Each layer constituting the resin film for terminal 10 will be described in detail below.
[0033] <First sealant layer> In this embodiment, the first sealant layer 1 is a layer that is bonded to a part of the outer circumferential surface of the metal terminal 14 by heat sealing (thermal fusion).
[0034] For example, a film containing a thermoplastic resin such as a polyolefin resin, a polyamide resin, a polyester resin, a polycarbonate resin, a polyphenylene ether resin, a polyacetal resin, a polystyrene resin, a polyvinyl chloride resin, or a polyvinyl acetate resin can be used as the first sealant layer 1. By blending the various resins listed above to form a polymer alloy, it is possible to control the sealing suitability and heat resistance.
[0035] Among them, it is preferable to use a film containing a polyolefin resin (hereinafter also referred to as a "polyolefin film") or a film containing a polyester resin (hereinafter also referred to as a "polyester film"). In this case, the sealing property for the metal terminal and the outer bag is improved. In addition, since the polyolefin film and the polyester film have heat resistance, the terminal resin film 10 can further improve the heat resistance of the all-solid-state battery.
[0036] Examples of polyolefin resins include polyolefin resins such as low-density, medium-density, or high-density polyethylene, ethylene-α-olefin copolymer, polypropylene, block or random copolymers containing propylene as a copolymerization component, and propylene-α-olefin copolymer. The polyolefin resin may be an acid-modified polyolefin resin obtained by modifying a polyolefin resin with an acid or glycidyl. In particular, the first sealant layer 1 is preferably an acid-modified polyolefin resin layer containing an acid-modified polyolefin resin. In this case, the acid-modified polyolefin resin layer has excellent adhesion to metal, so that the adhesion between the resin film for terminal 10 and the metal terminal can be further improved.
[0037] Examples of polyester resins include polyethylene terephthalate (PET) resin, polybutylene terephthalate (PBT) resin, polyethylene naphthalate (PEN) resin, polybutylene naphthalate (PBN) resin, and copolymers thereof. These polyester resins may be used alone or in combination of two or more. In addition, copolymers of any acid and glycol may be used.
[0038] The first sealant layer 1 may further contain additives such as antioxidants, slip agents, flame retardants, antiblocking agents, light stabilizers, dehydrating agents, tackifiers, crystal nucleating agents, plasticizers, etc., as necessary, in order to impart sealing properties, heat resistance, and other functionalities.
[0039] The melting point of the first sealant layer 1 is not particularly limited, but is preferably 150° C. or higher, more preferably 155° C. or higher, and even more preferably 160° C. or higher. When the melting point of the first sealant layer 1 is 150° C. or higher, even if the terminal resin film 10 is used in a high-temperature environment, the decrease in the seal strength of the terminal resin film 10 with respect to the metal terminal can be suppressed. Therefore, when the all-solid-state battery contains a sulfide-based solid electrolyte as a solid electrolyte in an outer bag, even if gas such as hydrogen sulfide is generated by a reaction between moisture and the sulfide-based solid electrolyte in the outer bag of the all-solid-state battery, leakage of such gas can be further suppressed.
[0040] The melting point of the first sealant layer 1 is preferably 250°C or less, more preferably 240°C or less, and even more preferably 230°C or less. In this case, the melting point of the first sealant layer 1 being 250°C or less can reduce the heat sealing temperature. Therefore, when the terminal resin film 10 is heat sealed to the metal terminal, the generation of air bubbles in the first sealant layer 1 can be more suppressed. Therefore, the decrease in the seal strength and barrier property of the terminal resin film 10 to the metal terminal is more suppressed. Therefore, the terminal resin film 10 can more sufficiently maintain the sealability of the outer bag of the all-solid-state battery. In addition, the terminal resin film 10 can also suppress the intrusion of moisture through the terminal resin film 10.
[0041] The thickness of the first sealant layer 1 is not particularly limited, but is preferably 10 to 200 μm, and more preferably 20 to 150 μm. When the thickness of the first sealant layer 1 is 10 μm or more, the gap between the metal terminal and the resin film for terminal 10 is easily filled with the resin constituting the first sealant layer 1. Furthermore, when the thickness of the first sealant layer 1 is 200 μm or less, the amount of heat required to melt the first sealant layer 1 can be reduced, so that the resin film for terminal 10 can be sealed to the metal terminal at a low temperature and in a short time, and the takt time can be shortened, thereby further improving productivity.
[0042] The thickness of the first sealant layer 1 may be greater than or equal to the thickness of the second sealant layer 3, but is preferably greater than the thickness of the second sealant layer 3. When the thickness of the resin film for terminal 10 is the same, the thickness of the first sealant layer 1 greater than the thickness of the second sealant layer 3 allows the amount of resin that fills the gap between the first sealant layer 1 and the metal terminal when the resin film for terminal 10 is heat-sealed to the metal terminal at high temperature to be greater than that of the second sealant layer 3, making it easier to fill the gap. In addition, it is preferable that the first sealant layer 1 and the second sealant layer 3 have the same thickness and contain the same resin. In this case, the first sealant layer 1 can be used as the second sealant layer 3 and the second sealant layer 3 can be used as the first sealant layer 1, and when fusing the resin film for terminal 10 to the metal terminal, it is not necessary to distinguish between the first sealant layer 1 and the second sealant layer 2, and the fusing process can be performed efficiently. Here, it is preferable that the resin contained in the first sealant layer 1 and the second sealant layer 3 is an acid-modified polyolefin resin. In this case, even when the second sealant layer 3 is heat-sealed to the metal terminal, the adhesion between the metal terminal and the resin film for terminal is improved.
[0043] <Insulating layer 2> The insulating layer 2 is a layer for suppressing thinning (sealing shrinkage) of the resin film for terminal during heat sealing and for ensuring insulation between the metal terminal and the metal layer of the exterior material.
[0044] For example, a film containing a thermoplastic resin such as a polyolefin resin, a polyamide resin, a polyester resin, a polycarbonate resin, a polyphenylene ether resin, a polyacetal resin, a polystyrene resin, a polyvinyl chloride resin, or a polyvinyl acetate resin can be used as the insulating layer 2. By blending the various resins listed above to form a polymer alloy, it is possible to control the sealing suitability and heat resistance.
[0045] Among them, it is preferable to use a polyolefin film or a polyester film. In this case, since the polyolefin film or the polyester film has heat resistance, the terminal resin film 10 can further improve the heat resistance of the all-solid-state battery.
[0046] In addition, the insulating layer 2 may further contain additives such as antioxidants, slip agents, flame retardants, antiblocking agents, light stabilizers, dehydrating agents, tackifiers, crystal nucleating agents, colorants, and plasticizers as necessary to impart sealing properties, heat resistance, and other functionalities.
[0047] The melting point of the insulating layer 2 is not particularly limited, but is preferably 150° C. or higher, more preferably 155° C. or higher, and even more preferably 160° C. or higher. When the melting point of the insulating layer 2 is 150° C. or higher, even if the terminal resin film 10 is used in a high-temperature environment, it is possible to suppress a decrease in the seal strength of the terminal resin film 10 with respect to the metal terminal. Therefore, when the all-solid-state battery contains a sulfide-based solid electrolyte as a solid electrolyte in an outer bag, even if gas such as hydrogen sulfide is generated by a reaction between moisture and the sulfide-based solid electrolyte in the outer bag of the all-solid-state battery, leakage of such gas can be further suppressed.
[0048] The melting point of the insulating layer 2 is preferably 250° C. or lower, more preferably 240° C. or lower, and even more preferably 230° C. or lower.
[0049] The melting point of the insulating layer 2 may be higher than the melting point of the resin contained in the first sealant layer 1 and the second sealant layer 3, or may be lower than the melting point of the resin contained in the first sealant layer 1 and the second sealant layer 3, but is preferably higher than the melting point of the resin contained in the first sealant layer 1 and the second sealant layer. In this case, when the resin film for terminal 10 is heat-sealed to an exterior material including a barrier layer made of a metal layer, sealing thinning (thinning) of the insulating layer 2 can be suppressed, making it easier to ensure insulation between the barrier layer of the exterior material and the metal terminal.
[0050] The thickness of the insulating layer 2 is not particularly limited, but is preferably 10 to 200 μm, and more preferably 20 to 150 μm. When the thickness of the insulating layer 2 is 10 μm or more, sufficient insulation can be obtained. When the thickness of the insulating layer 2 is 100 μm or less, the amount of water vapor penetrating from the peripheral portion of the resin film for terminal 10 can be reduced.
[0051] <Second sealant layer> In this embodiment, the second sealant layer 3 is a layer that is heat sealed (thermally fused) to the exterior bag of the all-solid-state battery.
[0052] For example, a film containing a thermoplastic resin such as a polyolefin resin, a polyamide resin, a polyester resin, a polycarbonate resin, a polyphenylene ether resin, a polyacetal resin, a polystyrene resin, a polyvinyl chloride resin, or a polyvinyl acetate resin can be used as the second sealant layer 3. By blending the various resins listed above to form a polymer alloy, it is possible to control the sealing suitability and heat resistance.
[0053] Among them, it is preferable to use a polyolefin film or a polyester film. In this case, the sealing property for the metal terminal and the outer bag is improved. In addition, since the polyolefin film and the polyester film have heat resistance, the terminal resin film 10 can further improve the heat resistance of the all-solid-state battery.
[0054] Examples of polyolefin resins include polyolefin resins such as low-density, medium-density, or high-density polyethylene, ethylene-α-olefin copolymer, polypropylene, block or random copolymers containing propylene as a copolymerization component, and propylene-α-olefin copolymer. The polyolefin resin may be an acid-modified polyolefin resin obtained by modifying a polyolefin resin with an acid or glycidyl.
[0055] Examples of polyester resins include polyethylene terephthalate (PET) resin, polybutylene terephthalate (PBT) resin, polyethylene naphthalate (PEN) resin, polybutylene naphthalate (PBN) resin, and copolymers thereof. These polyester resins may be used alone or in combination of two or more. In addition, copolymers of any acid and glycol may be used.
[0056] When the first sealant layer 1 and the insulating layer 2 are made of polyolefin films, it is preferable that the second sealant layer 3 is also made of a polyolefin film. In this case, a laminate film consisting of the first sealant layer 1, the insulating layer 2, and the second sealant layer 3 can be produced by co-extrusion, and the adhesive strength between the layers can be increased. In addition, when the first sealant layer 1 and the insulating layer 2 are made of polyester films, it is preferable that the second sealant layer 3 is also made of a polyester film. In this case, good adhesiveness can be obtained when the first sealant layer 1, the insulating layer 2, and the second sealant layer 3 are bonded with a heat-resistant polyester adhesive.
[0057] Furthermore, the second sealant layer 3 may further contain additives such as antioxidants, slip agents, flame retardants, antiblocking agents, light stabilizers, dehydrating agents, tackifiers, crystal nucleating agents, plasticizers, etc., as necessary, in order to impart sealing properties, heat resistance, and other functionalities.
[0058] The melting point of the second sealant layer 3 is not particularly limited, but is preferably 150° C. or higher, more preferably 155° C. or higher, and even more preferably 160° C. or higher. When the melting point of the second sealant layer 3 is 150° C. or higher, even if the terminal resin film 10 is used in a high-temperature environment, the decrease in the seal strength of the terminal resin film 10 with respect to the metal terminal can be suppressed. Therefore, when the all-solid-state battery contains a sulfide-based solid electrolyte as a solid electrolyte in an outer bag, even if gas such as hydrogen sulfide is generated by a reaction between moisture and the sulfide-based solid electrolyte in the outer bag of the all-solid-state battery, leakage of such gas can be further suppressed.
[0059] The melting point of the second sealant layer 3 is preferably 250°C or less, more preferably 240°C or less, and even more preferably 230°C or less. In this case, the melting point of the second sealant layer 3 is 250°C or less, so that the heat sealing temperature can be lowered. Therefore, when the terminal resin film 10 is heat sealed to the outer bag, the generation of air bubbles in the second sealant layer 1 can be more suppressed. Therefore, the decrease in the seal strength and barrier property of the terminal resin film 10 to the metal terminal is more suppressed. Therefore, the terminal resin film 10 can more sufficiently maintain the sealability of the outer bag of the all-solid-state battery. In addition, the terminal resin film 10 can also suppress the intrusion of moisture through the terminal resin film 10.
[0060] The melting point of the second sealant layer 3 may be the same as or different from the melting point of the first sealant layer 1, but is preferably the same.
[0061] The thickness of the second sealant layer 3 is not particularly limited, but is preferably 10 to 200 μm, and more preferably 20 to 150 μm. When the thickness of the second sealant layer 3 is 10 μm or more, sufficient seal strength can be obtained. When the thickness of the second sealant layer 3 is 200 μm or less, the amount of heat required to melt the second sealant layer 3 can be reduced, so that the sealing of the terminal resin film 10 to the outer bag of the all-solid-state battery can be performed at a low temperature and in a short time, and the tact time can be shortened, thereby further improving productivity.
[0062] <Hydrogen sulfide decomposition and adsorption material> When the terminal resin film 10 is used in an all-solid-state battery having a sulfide-based solid electrolyte, at least one of the layers constituting the terminal resin film 10 of the present embodiment may contain a hydrogen sulfide decomposition / adsorption material that decomposes or adsorbs hydrogen sulfide. In this case, even if hydrogen sulfide is generated by reaction between water and a sulfide-based solid electrolyte in the all-solid-state battery, the hydrogen sulfide is prevented from permeating the terminal resin film 10. The hydrogen sulfide decomposition / adsorption material is contained in, for example, the first sealant layer 1, the insulating layer 2, the second sealant layer 3, or the adhesive layer.
[0063] Examples of hydrogen sulfide decomposition and adsorption materials include zinc oxide, amorphous metal silicates (mainly those in which the metal is copper or zinc), hydrates of zirconium and tantanide elements, tetravalent metal phosphates (particularly those in which the metal is copper), mixtures of zeolite and zinc ions, mixtures of zeolite, zinc oxide, and copper (II) oxide, potassium permanganate, sodium permanganate, silver sulfate, silver acetate, aluminum oxide, iron hydroxide, isocyanate compounds, aluminum silicate, potassium aluminum sulfate, zeolite, activated carbon, amine compounds, and ionomers. In addition, the hydrogen sulfide decomposition and adsorption material is preferably one that contains zinc oxide (ZnO) and / or zinc ions, from the viewpoints of ease of detoxifying hydrogen sulfide, cost, and ease of handling. The hydrogen sulfide decomposition and adsorption material can be used alone or in combination of two or more types.
[0064] The hydrogen sulfide decomposition and adsorption material may be a deodorizer that has a deodorizing effect on hydrogen sulfide, such as "Daimshoo PE-M 3000-Z" (polyethylene masterbatch product) manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd., "Kesmon" manufactured by Toagosei Co., Ltd., "Shoe Cleanse" manufactured by Rasa Kogyo Co., Ltd., and "Dashlight ZU" and "Dashlight CZU" manufactured by Sinanen Zeomic Co., Ltd.
[0065] Metal soap such as zinc stearate may be added to the layer containing the hydrogen sulfide decomposition adsorption material in order to improve the dispersibility of the hydrogen sulfide decomposition adsorption material. By using the hydrogen sulfide decomposition adsorption material in combination with a metal soap, the dispersibility of the hydrogen sulfide decomposition adsorption material in the layer can be increased, making it difficult for the effect of detoxifying hydrogen sulfide to be biased, and making it easier to suppress a decrease in the function (e.g., adhesion strength, seal strength, etc.) of the layer containing the hydrogen sulfide decomposition adsorption material.
[0066] The hydrogen sulfide decomposition / adsorption material may be used in the form of a master batch. When the hydrogen sulfide decomposition-adsorbing material is blended in at least one of the first sealant layer 1, the insulating layer 2, the second sealant layer 3, and the adhesive layer, a high-concentration blend may be prepared in advance as a master batch, and then the master batch may be blended in the resin of at least one of the first sealant layer 1, the insulating layer 2, the second sealant layer 3, and the adhesive layer so as to have an appropriate concentration. The hydrogen sulfide decomposition-adsorbing material is preferably blended in the insulating layer 2. In this case, since the hydrogen sulfide decomposition-adsorbing material is not blended in the first sealant layer 1 and the second sealant layer 3, it is possible to more effectively prevent the strength between the first sealant layer 1 of the resin film for terminal and the metal terminal from decreasing, and it is also possible to more effectively prevent the strength between the second sealant layer 3 of the resin film for terminal and the exterior material from decreasing. The hydrogen sulfide decomposition-adsorbing material may be blended in the second sealant layer 3. Even in this case, since the hydrogen sulfide decomposition-adsorbing material is not blended in the first sealant layer 1, it is possible to more effectively prevent the strength between the first sealant layer 1 of the resin film for terminal and the metal terminal from decreasing. When the hydrogen sulfide decomposition and adsorption material is blended in the adhesive layer, it may be blended directly in the coating liquid when the adhesive layer is coated, or when the adhesive layer is formed by extrusion or the like, it may be blended in a master batch prepared in the same manner as the first sealant layer 1. When preparing a master batch, the resin that can be used may be a thermoplastic resin such as a polyolefin resin, a polyamide resin, a polyester resin, a polycarbonate resin, a polyphenylene ether resin, a polyacetal resin, a polystyrene resin, a polyvinyl chloride resin, or a polyvinyl acetate resin.
[0067] The content of the hydrogen sulfide decomposition adsorption material in the layer containing the hydrogen sulfide decomposition adsorption material may be 0.01% by mass to 30% by mass, 0.05% by mass to 20% by mass, or 0.1% by mass to 15% by mass, based on the total amount of the layer. When the content of the hydrogen sulfide decomposition adsorption material is equal to or more than the lower limit, the effect of detoxifying hydrogen sulfide is easily obtained, and when the content is equal to or less than the upper limit, deterioration of the function (e.g., adhesion strength, seal strength, etc.) of the layer containing the hydrogen sulfide decomposition adsorption material can be suppressed.
[0068] [Method of manufacturing resin film for terminals] Next, a description will be given of a method for producing the resin film for terminal 10. However, the method for producing the resin film for terminal 10 is not limited to the following method.
[0069] The resin film for a terminal 10 can be obtained, for example, by co-extruding the first sealant layer 1, the insulating layer 2 and the second sealant layer 3.
[0070] The resin film for terminal 10 can also be obtained by previously preparing the first sealant layer 1, the insulating layer 2, and the second sealant layer 3, and then layering and thermally laminating them. The temperature during the thermal lamination may be any temperature as long as it is higher than the melting points of the first sealant layer 1 and the second sealant layer 3 .
[0071] When the resin film 10 for terminals has a first sealant layer 1, an adhesive layer, an insulating layer 2, and a second sealant layer 3, a two-layer film consisting of the insulating layer 2 and the second sealant layer 3 may be formed in advance, and then the two-layer film and the first sealant layer 1 may be laminated using an adhesive by a dry lamination method using an adhesive.
[0072] [Method of fusing resin film for terminals] The fusion process for melt-bonding the resin film for terminal 10 shown in FIG. 1 to the exterior bag will be described.
[0073] First, a fusion process is performed to melt and bond the resin film 10 for terminals to the metal terminals 14. At this time, the first sealant layer 1 of the resin film 10 for terminals shown in Fig. 1 is faced to the metal terminals 14, and the resin film 10 for terminals and the metal terminals 14 are thermally fused together while simultaneously melting the first sealant layer 1 by heating and bonding the first sealant layer 1 to the metal terminals 14 by applying pressure (see Fig. 3).
[0074] In the fusion treatment, from the viewpoint of obtaining sufficient adhesion and sealing property between the resin film for terminal 10 and the metal terminal 14, it is preferable to heat to a temperature of the melting point of the first sealant layer 1 +20° C. or more.
[0075] The heating temperature of the resin film 10 for terminal may be, for example, 155 to 285° C. The heat fusion time can be determined in consideration of the adhesion to the metal terminal 14 and productivity. The heat fusion time can be appropriately set within the range of, for example, 1 to 60 seconds.
[0076] Next, a fusion process is performed to melt and bond the resin film 10 for terminals and the exterior material 13 (see FIG. 2). Specifically, the resin film 10 for terminals and the exterior material are thermally fused together while simultaneously melting the second sealant layer 3 by heating and bonding the second sealant layer 3 to the exterior material by applying pressure.
[0077] In the fusion treatment, the second sealant layer 3 of the resin film for terminals 10 and the sealant layer of the exterior material 13 are heated and melted. At this time, the heating temperature may be a temperature at which both the second sealant layer 3 of the resin film for terminals 10 and the sealant layer of the exterior material 13 melt, but from the viewpoint of obtaining sufficient adhesion and sealing properties of the second sealant layer 3 of the resin film for terminals 10 and the sealant layer of the exterior material 13, the heating temperature is preferably set to a temperature of the melting point of the sealant layer with a higher melting point out of the second sealant layer 3 of the resin film for terminals 10 and the sealant layer of the exterior material 13 + 20°C or more.
[0078] The heating temperature of the resin film for terminal 10 may be, for example, 155 to 285° C. The heat fusion time can be determined in consideration of the adhesion to the exterior material 13 and productivity. The heat fusion time can be appropriately set within the range of, for example, 1 to 60 seconds.
[0079] [All-solid battery] FIG. 2 is a perspective view showing one embodiment of an all-solid-state battery produced using the above-mentioned resin film for terminal. As shown in FIG. 2, the all-solid-state battery 50 includes a battery body 11 having a sulfide-based electrolyte as a solid electrolyte, two metal terminals (current extraction terminals) 14 for extracting current from the battery body 11 to the outside, a resin film for terminal 10, and an exterior bag 54 for housing the battery body 11 in an airtight state. The exterior bag 54 is used as a container for housing the battery body 11. The resin film for terminal 10 is bonded to a part of the outer peripheral surface of the metal terminal 14, and the metal terminal 14 is sandwiched by the exterior bag 54 via the resin film for terminal 10. In the resin film for terminal 10, the first sealant layer 3 is bonded to the metal terminal 14, and the second sealant layer 3 is bonded to the exterior bag 54.
[0080] According to the all-solid-state battery 50, the terminal resin film 10 is bonded to the metal terminal 14 by heat sealing. Here, according to the terminal resin film 10, when the terminal resin film 10 is heat-sealed to the metal terminal 14, the generation of air bubbles in the terminal resin film 10 can be suppressed. Therefore, according to the all-solid-state battery 50, the occurrence of rough and dense parts in the terminal resin film 10 and the decrease in the seal strength to the metal terminal at the rough parts are suppressed. Therefore, even if the battery body 11 expands due to the use of the all-solid-state battery 50 in a high-temperature environment and a force acts on the exterior bag 54 to open it, the all-solid-state battery 50 can maintain the sealed state of the exterior bag 54 by the terminal resin film 10. As a result, even if hydrogen sulfide is generated in the exterior bag 54, the hydrogen sulfide is suppressed from leaking from the exterior bag 54. In addition, the first sealant layer 1 suppresses the generation of air bubbles that easily become a passage for moisture, so that the intrusion of moisture from the outside of the terminal resin film 10 is suppressed. As a result, it is possible to suppress the generation of hydrogen sulfide due to a reaction between moisture and the sulfide-based electrolyte.
[0081] The battery body 11, the metal terminals 14, and the exterior bag 54 will be described in detail below.
[0082] <Battery body> The battery body 11 has at least one power generating element consisting of a positive electrode, a solid electrolyte, and a negative electrode. The solid electrolyte is not limited to a sulfide-based solid electrolyte, and may be an oxide-based solid electrolyte or the like. <Metal terminal> 2 and 3, the pair of metal terminals 14 includes a metal terminal body 14-1 and a corrosion prevention layer 14-2. Of the pair of metal terminal bodies 14-1, one metal terminal body 14-1 is electrically connected to the positive electrode of the battery body 11, and the other metal terminal body 14-1 is electrically connected to the negative electrode of the battery body 11. The pair of metal terminal bodies 14-1 extend in a direction away from the battery body 11, and a part of each of the metal terminal bodies 14-1 is exposed from the exterior material 13. The shape of the pair of metal terminal bodies 14-1 may be, for example, a flat plate shape.
[0083] The material of the metal terminal body 14-1 may be a metal, which may be selected in consideration of the structure of the battery body 11 and the materials of each of the components of the battery body 11.
[0084] When the all-solid-state battery 50 is a lithium-ion secondary battery, aluminum can be used as the positive electrode current collector, and copper can be used as the negative electrode current collector. When the all-solid-state battery 50 is a lithium-ion secondary battery, the material of the metal terminal body 14-1 connected to the positive electrode of the battery body 11 is preferably aluminum. The material of the metal terminal body 14-1 connected to the positive electrode of the battery body 11 may be an aluminum material with a purity of 97% or more, such as 1N30. Furthermore, when the metal terminal body 14-1 is bent, an O material that has been annealed sufficiently to add flexibility may be used. The material of the metal terminal body 14-1 connected to the negative electrode of the battery body 11 may be, for example, copper with a nickel plating layer formed on the surface, or nickel.
[0085] The thickness of the metal terminal body 14-1 can be determined according to the size and capacity of the all-solid-state battery 50. When the all-solid-state battery 50 is small, the thickness of the metal terminal body 14-1 may be 50 μm or more. In the case of a large all-solid-state battery for power storage, in-vehicle use, etc., the thickness of the metal terminal body 14-1 can be appropriately set within the range of 100 to 1000 μm.
[0086] The corrosion prevention layer 14-2 is disposed so as to cover the surface of the metal terminal body 14-1. In the all-solid-state battery 50, the corrosion prevention layer 14-2 is a layer for suppressing corrosion of the metal terminal body 14-1 due to corrosive components such as hydrogen sulfide.
[0087] <Outer bag> As shown in Fig. 2, the exterior bag 54 is obtained by overlapping two sheets of exterior materials 13 and heat-sealing the overlapping peripheral portions. The exterior bag 54 can also be obtained by folding the exterior material 13 in half and heat-sealing the overlapping peripheral portions. The exterior material 13 includes, from the battery body 11 side, a sealant layer 21, a first adhesive layer 22, a corrosion prevention treatment layer 23-1, a barrier layer 24, a corrosion prevention treatment layer 23-2, a second adhesive layer 25, and a base material layer 26 in this order (see Fig. 4).
[0088] The sealant layer 21 is a layer that imparts heat sealing to the exterior material 13, and is disposed on the inside during assembly of the all-solid-state battery 50 and is heat sealed (thermal fusion). For example, a polyolefin resin or an acid-modified polyolefin resin obtained by graft-modifying a polyolefin resin with maleic anhydride or the like can be used as the base material of the sealant layer 21. As the polyolefin resin, low-density, medium-density, and high-density polyethylene; ethylene-α-olefin copolymer; homo-, block-, or random polypropylene; propylene-α-olefin copolymer, etc. can be used. Among these, it is preferable that the polyolefin resin contains polypropylene. These polyolefin resins can be used alone or in combination of two or more.
[0089] The sealant layer 21 may be a single layer film or a multilayer film in which multiple layers are laminated, depending on the required function. Specifically, it may be a multilayer film in which a resin such as an ethylene-cyclic olefin copolymer or polymethylpentene is interposed in order to impart moisture resistance. The sealant layer 21 may contain various additives (flame retardants, slip agents, antiblocking agents, antioxidants, light stabilizers, tackifiers, etc.).
[0090] The thickness of the sealant layer 21 is preferably 10 to 150 μm, and more preferably 30 to 80 μm. When the thickness of the sealant layer 21 is 10 μm or more, the exterior material 13 can have sufficient adhesion to the exterior material 13 or the resin film for terminal 10. Furthermore, when the thickness of the sealant layer 21 is 150 μm or less, the cost of the exterior material 13 can be reduced.
[0091] For the first adhesive layer 22, a known adhesive such as a dry lamination adhesive or an acid-modified heat-fusible resin can be appropriately selected and used.
[0092] As shown in Figure 4, it is preferable from the viewpoint of performance to form the anti-corrosion treatment layers 23-1, 23-2 on both sides of the barrier layer 24, but from the viewpoint of reducing costs, the anti-corrosion treatment layer 23-1 may be placed only on the side of the barrier layer 24 located on the first adhesive layer 22 side.
[0093] The barrier layer 24 may be a metal layer having electrical conductivity. Examples of materials for the barrier layer 24 include aluminum and stainless steel, and aluminum is preferred from the standpoints of cost, mass (density), and the like.
[0094] For the second adhesive layer 25, a polyurethane adhesive containing polyester polyol, polyether polyol, acrylic polyol, or the like as a main component can be used.
[0095] The base material layer 26 may be a single layer or a multilayer of nylon, polyethylene terephthalate (PET), etc. Like the sealant layer 21, the base material layer 26 may contain various additives (such as a flame retardant, a slip agent, an antiblocking agent, an antioxidant, a light stabilizer, and a tackifier).
[0096] Moreover, the exterior material 13 may further include a protective layer (not shown) for protecting the base material layer 26 on the surface of the base material layer 26 opposite to the sealant layer 21 .
[0097] Moreover, in the exterior material 13, instead of the first adhesive layer 22, an adhesive resin layer may be used.
[0098] At least one of the layers constituting the exterior material 13 of this embodiment may contain a hydrogen sulfide decomposition / adsorption material, similar to the terminal resin film 10. In this case, even if hydrogen sulfide is generated by reaction between water and a sulfide-based solid electrolyte in the all-solid-state battery 50, the hydrogen sulfide is prevented from permeating the exterior material 13. The hydrogen sulfide decomposition / adsorption material is contained in, for example, the first adhesive layer 22, the second adhesive layer 25, the sealant layer 21, or at least one of these. In particular, the hydrogen sulfide decomposition / adsorption material is preferably contained in the sealant layer 21. In this case, the hydrogen sulfide is effectively prevented from permeating the exterior material 13.
[0099] Although the preferred embodiments of the present disclosure have been described in detail above, the present disclosure is not limited to the above-described embodiments. For example, the resin film 10 for a terminal includes a first sealant layer 1, an insulating layer 2, and a second sealant layer 3, but when the outer bag 54 does not include a metal layer, the resin film 10 for a terminal does not need to include the insulating layer 2. The resin film for a terminal may be configured as a single layer film, as in the case of the resin film 110 for a terminal shown in FIG. 5. In this case, the resin film 110 for a terminal has a moisture content of 2700 mass ppm or less. The resin film 110 for a terminal may be configured as any one of the first sealant layer 1, the insulating layer 2, or the second sealant layer 3. EXAMPLES
[0100] The present disclosure will be described more specifically below based on examples, but the present disclosure is not limited to the following examples.
[0101] Example 1 A film made of acid-modified polypropylene (thickness: 25 μm, melting point: 140° C.), a film made of polypropylene (thickness: 50 μm, melting point: 164° C.), and a film made of acid-modified polypropylene (thickness: 25 μm, melting point: 140° C.) were co-extruded to obtain a 100 μm thick polyolefin film 1 (PO film 1). The water content of the obtained PO film 1 was 358 ppm by mass.
[0102] Example 2 A resin film for terminals was obtained in the same manner as in Example 1, except that the PO film 1 was changed to a polyolefin film 2 (PO film 2) made of a polypropylene-polyethylene random copolymer (manufactured by Futamura Chemical Co., Ltd., product name: FHK2, melting point: 135°C) and the thickness was changed from 100 μm to 40 μm. The moisture content of the obtained resin film for terminals was 516 ppm by mass.
[0103] Example 3 A resin film for terminals was obtained in the same manner as in Example 1, except that the PO film 1 was changed to a polyester film (polyester film 1) made of polyethylene terephthalate (manufactured by Unitika Ltd., product name: Emblet, melting point: 257°C) and the thickness was changed from 100 μm to 25 μm. The moisture content of the obtained resin film for terminals was 2682 ppm by mass.
[0104] Example 4 A resin film for terminals was obtained in the same manner as in Example 1, except that the PO film 1 was changed to a polyester film (polyester film 2) made of polyethylene naphthalate (manufactured by Toyobo Co., Ltd., product name: Teonex, melting point: 265°C) and the thickness was changed from 100 μm to 25 μm. The moisture content of the obtained resin film for terminals was 2637 ppm by mass.
[0105] Example 5 A resin film for terminals was obtained in the same manner as in Example 1, except that the PO film 1 was changed to a polyester film (polyester film 3) made of a copolymer of multiple types of polyethylene terephthalate (melting point: 210°C) and the thickness was changed from 100 μm to 25 μm. The moisture content of the obtained resin film for terminals was 1648 ppm by mass.
[0106] Example 6 A resin film for terminals was obtained in the same manner as in Example 1, except that the PO film 1 was changed to a polyolefin film 3 (PO film 3) consisting of a laminate obtained by co-extrusion of a film made of acid-modified polypropylene (thickness: 25 μm, melting point: 165° C.), a film made of polypropylene (thickness: 50 μm, melting point: 165° C.), and a film made of acid-modified polypropylene (thickness: 25 μm, melting point: 165° C.). The moisture content of the obtained resin film for terminals was 546 ppm by mass.
[0107] Comparative Example 1 A resin film for terminals was obtained in the same manner as in Example 1, except that the PO film 1 was changed to a polyamide film (PA film) made of nylon 6 (manufactured by Toyobo Co., Ltd., product name: Harden N1102, melting point: 225°C) and the thickness was changed from 100 μm to 25 μm. The moisture content of the obtained resin film for terminals was 23729 ppm by mass. The moisture content was measured as follows. That is, the resin film for terminals cut into 10 cm squares was left in an environment of 23°C / 50%RH for two days, and then heated using a thermal moisture vaporizer (manufactured by HIRANUMA Co., Ltd., product name: EV-2000) set at 300°C, and the amount of moisture generated was measured using a trace moisture measuring device (Karl Fischer: "AQ-2100" manufactured by HIRANUMA Co., Ltd.). At this time, dry N2 gas was used as the carrier gas. Then, the moisture content was calculated based on the following formula using the moisture amount value measured as described above. Moisture content (mass ppm) = measured moisture amount (g) / mass of resin film for terminals (g)
[0108] <Evaluation of resin film for terminals> The resin film for terminals was cut into a size of 120 mm x 60 mm, folded in half, and both ends of the resin film for terminals in the longitudinal direction were overlapped. These ends were heat-sealed for 10 seconds at a temperature of the melting point of the resin film for terminals + 20°C while applying a pressure of 0.6 MPa, forming a heat-sealed part with a width of 10 mm (shaded part in Figure 6), and a structure was produced. The structure was then stored at room temperature for 12 hours. Then, the center part in the longitudinal direction of the heat-sealed part was cut out from the structure with a width of 15 mm x 30 mm (see Figure 6) to produce an evaluation sample. Then, this evaluation sample was separated into two separated pieces at the fused part. The fused part of the separated pieces was visually observed, and the state of bubble generation in the resin film for terminals was evaluated based on the following criteria. The results are shown in Table 1. In addition, when the resin film for the terminal is a multilayer film, the "melting point of the resin film for the terminal" refers to the melting point of the sealant layer that is the layer with the lowest melting point and is located outermost among the layers constituting the multilayer film. (Evaluation Criteria) ◎: No air bubbles are observed ○: Localized air bubbles are observed ×: Air bubbles are observed all over the surface
[0109] [Table 1]
[0110] The results shown in Table 1 show that the resin films for terminals of Examples 1 to 6, which have a moisture content of 2700 ppm by mass or less, suppress the generation of air bubbles compared to the resin film for terminals of Comparative Example 1, which has a moisture content of more than 2700 ppm by mass.
[0111] Therefore, it was confirmed that the resin film for terminal of the all-solid-state battery according to the present disclosure can suppress the generation of air bubbles when heat-sealed to a metal terminal. [Explanation of symbols]
[0112] 1...first sealant layer (sealant layer), 2...insulating layer, 3...second sealant layer (sealant layer), 10, 110...resin film for terminal, 11...battery body, 14...metal terminal, 50...all-solid-state battery.
Claims
1. A resin film for a terminal of an all-solid-state battery that is bonded by heat sealing to an outer peripheral surface of a part of a metal terminal that is electrically connected to a battery body constituting an all-solid-state battery, A polyester film containing a polyester-based resin is provided, A resin film for a terminal of an all-solid-state battery, having a moisture content of 1648 ppm by mass or more and 2700 ppm by mass or less.
2. A multilayer film having an insulating layer and a sealant layer provided on at least one side of the insulating layer, The resin film for a terminal of an all-solid-state battery according to claim 1 , wherein the sealant layer is the polyester film.
3. The resin film for a terminal of an all-solid-state battery according to claim 1 or 2, which has a melting point of 250° C. or less.
4. The resin film for a terminal of an all-solid-state battery according to any one of claims 1 to 3, having a melting point of 150 ° C. or more.
5. A battery body including a solid electrolyte; A metal terminal electrically connected to the battery body; an outer bag that holds the metal terminals and accommodates the battery body; a resin film for a terminal that is bonded by heat sealing to a part of an outer peripheral surface of the metal terminal; The terminal resin film comprises the terminal resin film according to any one of claims 1 to 4.